KEEFEKTIPAN DARI MENGGUNAKAN STRATEGI CONTEXT CLUES PADA PEMAHAMAN MEMBACA SISWA KELAS SATU SMA MUHAMMADIYAH 1 PEKANBARU - Dita Herinovita Dita Herinovita; Syofia Delfi Syofia Delfi; Rumiri Aruan Rumiri Aruan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This experimental study aimed to find out the effect of using contexts clues strategy in reading comprehension. This experimental research was used one-group pretest-posttest design. The reason for conducted this research because students tend to used dictionary when they read English text in order to find the meaning of difficult word. However, they may not use dictionary or some stuff that can help them to understand English text in joining examination. This condition makes students difficult to comprehend the English text because they face different context. So, students should know about reading strategy to increase their reading comprehension without using dictionary or another instrument. One of the appropriate reading strategies to increase the students’ reading comprehension ability is context clue. The sample of this research was the first year students of SMA Muhammadiyah 1 Pekanbaru. The participants were 33 students as tryout class and 28 students as experiment class. The steps of research procedure are conducting pre-test, treatment, post-test and data analysis. The data analyzed by using t-test formula. The data analysis showed there is significant effect of using context clues strategy on reading comprehension. The finding also proved that in the pre-test students’ average score was only 71.17 and it improved to 84.00 in the post-test. Moreover, for the statistical analysis it was found out the T-observe 7.64 was higher than T-table. Base on this finding, it is suggested that context clues strategy can be used by teacher as an alternative strategy that can help students to increase their reading comprehension.Keywords: Context Clues, Reading Comprehension, Experimental Research, Reading Strategy